Assessing predetermined expectations in the standard sticky-price model: a Bayesian approach - Peter Welz (European Central Bank (ECB), 2006)
This paper analyses the empirical performance of a New Keynesian stickyprice model with delayed effects of monetary impulses on inflation and output for the German pre-EMU economy. The model is augmented with rule-ofthumb behaviour in consumption and price setting. Using recently developed Bayesian estimation techniques, endogenous persistence is found to play a dominant role in consumption whereas forward-looking behaviour is greater for inflation. The model's dynamics following a monetary shock and a preference shock are comparable to those of an identified VAR model.
Keywords: E43; E52; C51; 330; Bayesian estimation; DSGE-Model; identified VAR; predetermined expectations; Allgemeines Gleichgewicht; Stochastisches Wachstumsmodell; Preisrigidität; VAR-Modell; Wahrscheinlichkeitsrechnung; Theorie; Deutschland